Identification of Smad Response Elements in the Promoter of Goldfish FSHβ Gene and Evidence for Their Mediation of Activin and GnRH Stimulation of FSHβ Expression - Lau, Man-Tat; Lin, Sze-Wah; Ge, Wei (Frontiers in Endocrinology, 2012)
As an essential hormone regulating gonads in vertebrates, the biosynthesis and secretion of follicle-stimulating hormone (FSH) is controlled by a variety of endocrine and paracrine factors in both mammalian and non-mammalian vertebrates. Activin was initially discovered in the ovary for its specific stimulation of FSH secretion by the pituitary cells. Our earlier studies in fish have shown that activin stimulates FSHβ but suppresses LHβ expression in both the goldfish and zebrafish. Further experiments showed that the regulation of FSHβ in fish occurred at the promoter level involving Smads, in particular Smad3. To further understand the mechanisms by which activin/Smad regulates FSHβ transcription, the present study was undertaken to analyze the promoter of goldfish FSHβ gene (fshb) with the aim to identify potential cis-regulatory elements responsible for activin/Smad stimulation. Both serial deletion and site-directed mutagenesis were used, and the promoter activity was tested in the LβT2 cells, a murine gonadotroph cell line. The reporter constructs of goldfish FSHβ promoter-SEAP (secreted alkaline phosphatase) were co-transfected with an expression plasmid for Smads (2 or 3) followed by measurement of SEAP activity in the medium. Two putative Smad responsive elements (SRE) were identified in the promoter at distal and proximal regions, respectively. The distal site contained a consensus Smad binding element (SBE; AGAC, -1675/-1672) whereas the proximal site (GACCTTGA, -212/-205) was identical to an SF-1 binding site reported in humans, which was preceded by a sequence (AACACTGA) highly conserved between fish and mammals. The proximal site also seemed to be involved in mediating stimulation of FSHβ expression by gonadotropin-releasing hormone (GnRH) and its potential interaction with activin. In conclusion, we have identified two potential cis-regulatory elements in the promoter of goldfish FSHβ that are responsible for activin-induced expression of th